Evaluation of Cladophora vadorum antimicrobial activity collected from Tabalino lakes in Benghazi city, Libya on human pathogenic bacterial isolates - Alteerah, Munay A.; Loujanqi, Amnnah Kh. Loujanqi; Godeh, Masoud M. (Libyan Journal of Science &Technology, 2024)
This study was conducted using Cladophora vadorum (green algae), collected from Tabalino lakes in Benghazi to evaluate the effect of this algae on the growth of four strains of bacteria (Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, and Klebsiella pneumonia) using 5 types of organic solvents (ethanol, acetone, methanol, petroleum ether, and ethyl acetate). The effect of organic solvent extracts on the growth of the bacteria used was varied. The petroleum ether extract was the most effective against the growth of all the bacteria used. Ethanol, Acetone, and ethyl acetate were active against at least one or two of the tested bacteria. The inhibitory effect on other bacteria was different. S. aureus was found to be more sensitive by all the organic solvent extracts used. E. coli has resistance and did not give positive results against extracts used except petroleum ether extract, while K. pneumonia bacteria was not affected by all types of organic extracts used. Presence of many active substances in Cladophora vadorum methanol extract supports their placement among medicinal plants because of their medically influenced compounds.